Important knowledge for parents of children with heart disease: parent, nurse, and physician views. (20th January 2015) - Daily, Joshua; FitzGerald, Mike; Downing, Kimberly; King, Eileen; del Rey, Javier Gonzalez; Ittenbach, Richard; Marino, Bradley
Abstract: Objectives: Parental understanding of their children's heart disease is inadequate, which may contribute to poor health outcomes. The purpose of this study was to determine what parental knowledge is important in the care of children with heart disease from the perspective of parents, nurses, and physicians. Methods: Focus groups were formed with parents of children with single ventricle congenital heart disease (CHD), biventricular CHD, and heart transplantation, and with nurses and physicians who provide care for these children. A nominal group technique was used to identify and prioritise important parental knowledge items and themes. The voting data for each theme were reported by participant type – parent, nurse, and physician – and patient diagnosis – single ventricle CHD, biventricular CHD, and heart transplantation. Results: The following three themes were identified as important by all groups: recognition of and response to clinical deterioration, medications, and prognosis and plan . Additional themes that were unique to specific groups included the following: medical team members and interactions (parents), tests and labs (parents), neurodevelopmental outcomes and interventions (physicians), lifelong disease requiring lifelong follow-up (physicians and nurses), and diagnosis, physiology, and interventions (single ventricle and biventricular CHD). Conclusions: Parents, nurses, and physicians have both common and unique views regarding what parents should know to effectively care for their children with single ventricle CHD, biventricular CHD, or heart transplantation. Specific targeted parental education that incorporates these findings should be provided to each group. Further development of questionnaires regarding parental knowledge with appropriate content validity is warranted.